Siphonaptera associated with small mammals (Didelphimorphia, Chiroptera, and Rodentia) from northwestern Argentina - Lopez-Berrizbeitia, M. Fernanda; Diaz, M. Monica (THERYA, 2019)
Northwestern Argentina (NOA) is one of the least studied areas in Argentina with respect to ectoparasites of the order Siphonaptera; previous investigations, until this study, were scarce and specific. The objective of this study was to contribute to the knowledge of the diversity of siphonaptera that parasitize small mammals from the NOA, emphasizing in their systematics and distribution. Specimens of fleas collected in several localities of NOA, and stored in the â€œAnnexesâ€ of the Colección Mamíferos Lillo, Universidad Nacional de Tucuman, Argentina, were studied. Fleas were manually removed from the host pelage, fixed in alcohol 70 % and prepared following conventional techniques for later observation under microscope. For specimen identification, the original descriptions of species and subspecies were reviewed and compared with specimens stored in systematic collections. Nine families, 22 genera, 53 species, and eight subspecies were recorded. A new family, a new genus, and three new species are recorded for the first time in Argentina; five species are new for NOA and nine are new to science. The distribution of 11 species and two subspecies are extended in the NOA, new records are added to different provinces and new flea-hosts associations are reported. The greatest diversity of fleas in the Yungas is the reflection of one of the areas with the highest biodiversity in the Neotropical region, such as the Yungas forests, which also includes mammals, as sigmodontine rodents and bats among them. The similarity analysis among eco-regions showed a major faunistic congruence between the Yungas and the Dry Chaco. The greatest differentiation was given by the High Andes and Puna compared with the other eco-regions, probably because these areas are the least surveyed and with the lowest richness and abundance of small mammal species. From the total of 82 new flea-host associations, 81 belong to sigmodontine rodent hosts and one to a marsupial.